Better to be informed: Threatening bats increase recall of information. Issue 1 (2nd January 2020) - Greving, Hannah; Kimmerle, Joachim
ABSTRACT: Bats are fascinating wildlife species. Yet, many citizens tend to perceive them as threatening. Such perceptions could influence citizens' knowledge acquisition about bats. In terms of wildlife management, it is important to understand what citizens who perceive bats as threatening learn about bats. Evolutionarily, it is likely that humans process negative information about threatening bats more attentively as they may encounter them again in the future. Therefore, this study investigated how representations of bats as threatening affected participants' recall of information by comparing a threatening representation to other representations of bats as cute, neutral, and imperiled. We hypothesized and found that representations of bats as threatening elicited recall of more negative pieces of information and more pieces of information overall than representations of bats as imperiled, neutral, or cute. Thus, threatening bats increased citizens' knowledge acquisition. We discuss the implications for wildlife management.